2015
DOI: 10.1183/13993003.01699-2014
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of physical activity on COPD hospitalisation depend on intensity

Abstract: The present study aims to disentangle the independent effects of the quantity and the intensity of physical activity on the risk reduction of chronic obstructive pulmonary disease (COPD) hospitalisations.177 patients from the Phenotype Characterization and Course of COPD (PAC-COPD) cohort (mean±SD age 71±8 years, forced expiratory volume in 1 s 52±16% predicted) wore the SenseWear Pro 2 Armband accelerometer (BodyMedia, Pittsburgh, PA, USA) for eight consecutive days, providing data on quantity (steps per day,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 37 publications
6
51
3
5
Order By: Relevance
“…Our Internet-mediated, pedometer-based intervention focuses specifically on walking, a low-intensity PA that most patients can do. It has already been shown that a greater quantity of low-intensity PA reduces risk of COPD hospitalizations, whereas high-intensity PA does not result in risk reduction [15]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our Internet-mediated, pedometer-based intervention focuses specifically on walking, a low-intensity PA that most patients can do. It has already been shown that a greater quantity of low-intensity PA reduces risk of COPD hospitalizations, whereas high-intensity PA does not result in risk reduction [15]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a greater quantity of low-intensity PA reduces risk of COPD hospitalizations, whereas high-intensity PA does not result in risk reduction [15]. In a cohort of persons with COPD, those who walk the least have risks that are 2 and 6 times higher for acute exacerbations and COPD-related hospitalizations, respectively, compared to those who walk the most [12].…”
Section: Introductionmentioning
confidence: 99%
“…Data support that a range of types and intensities of PA beyond aerobic exercise, which is emphasized in pulmonary rehabilitation, may be beneficial in COPD [16]. Increased low-intensity PA was significantly associated with a decreased risk of COPD-related hospitalizations, whereas increased high-intensity PA demonstrated no benefit [17]. …”
Section: Introductionmentioning
confidence: 99%
“…International guidelines suggest that patients with COPD should walk at least 20 to 30 minutes every day (GOLD, 2016; The Australian Lung Foundation, 2012). Physical activity and exercise not only help patients with COPD to maintain their fitness levels but also decrease dyspnoea and fatigue developing during activity, increase walking distance and muscle strength and endurance, improve the quality of life, and decrease the frequency of exacerbations, length of hospital stay, use of health care services, and mortality rates (Breyer et al, 2010;de Blok et al, 2006;Donaire-Gonzalez et al, 2015;Garcia-Aymerich, Lange, Benet, Schnohr, & Anto, 2006;Kawagoshi et al, 2015;Martinez et al, 2014;Mendoza et al, 2015;Moy et al, 2015;Spruit et al, 2004;Vorrink, Kort, Troosters, & Lammers, 2011;Watz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%